2012
DOI: 10.1590/s0047-20852012000100004
|View full text |Cite
|
Sign up to set email alerts
|

Transtorno de estresse pós-traumático e a presença de recordações referentes à unidade de terapia intensiva

Abstract: rESUMo objetivo: Identificar a incidência de transtorno de estresse pós-traumático (TEPT) em pacientes submetidos à ventilação mecânica (VM) e analisar a sua relação com variáveis clíni-cas, demográficas e presença de recordações referentes à unidade de terapia intensiva (UTI). Método: Estudo prospectivo longitudinal realizado durante o período de um ano na UTI de um hospital-escola. A avaliação ocorreu três meses após a alta da UTI durante consulta ambulatorial. Os sujeitos foram avaliados utilizando-se um in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 23 publications
(63 reference statements)
0
9
0
12
Order By: Relevance
“…The mean age of enrolled patients ranged from 36.5 to 68.0 years; 27 studies reported a male predominance. Except for 4 studies conducted in Australia [20, 25, 33, 62], 2 conducted in Latin America [24, 29], 1 study conducted in Iran [22], and 4 studies in which location was not reported [30, 41, 46, 57], all other studies (77%) were conducted in the USA or Europe.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of enrolled patients ranged from 36.5 to 68.0 years; 27 studies reported a male predominance. Except for 4 studies conducted in Australia [20, 25, 33, 62], 2 conducted in Latin America [24, 29], 1 study conducted in Iran [22], and 4 studies in which location was not reported [30, 41, 46, 57], all other studies (77%) were conducted in the USA or Europe.…”
Section: Resultsmentioning
confidence: 99%
“…Tais sintomas podem ser considerados como estratégias emocionais, cognitivas e comportamentais para minimizar o desgaste provocado pelo evento. Os sintomas desse grupo caracterizam-se por esforços exercidos pelos pacientes para evitar pensamentos, sensações, atividades, pessoas e locais relacionados ao evento traumático (COSTA, 2012).…”
Section: Discussionunclassified
“…Within the Brazilian context, the scientific literature points to similar results regarding the consequences of ICU admission on patients' mental health, finding PTSD and anxiety and depression symptoms, which also affected patients' quality of life, associated to physical and psychological conditions (Calsavara, Costa, Nobre, & Teixeira, 2020;Costa, Marcon, & Rossi, 2012;Righy et al, 2019;Rosa et al 2019;Rovatti, Teodoro, & Castro, 2012;Teixeira et al, 2021). Costa et al (2012) and Rovatti et al (2012) found that patients' psychological symptoms also included affective or illusory memories, feelings of hopelessness, and fear and loss of control, which they experienced vividly, thus evoking anxiety and behavioral changes.…”
mentioning
confidence: 87%